2018
DOI: 10.1038/s41418-018-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune adaptor MyD88 deficiency prevents skin inflammation in SHARPIN-deficient mice

Abstract: Mice deficient in SHANK-associated RH domain-interacting protein (SHARPIN), a component of the linear ubiquitin chain assembly complex (LUBAC), develop a spontaneous inflammatory disorder with pathologic hallmarks similar to atopic dermatitis and psoriasis in humans. Previous studies identified the crucial role of components of the TNF and IL-1 signaling pathways in the progression of disease in SHARPIN-deficient mice. However, an innate immune adaptor or sensor that relates to the disease progression has rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…For immunoblot analysis of signaling components, supernatants were removed, and cells were washed once with PBS, followed by lysis in RIPA buffer and sample loading buffer. Proteins were separated by electrophoresis through 8%-12% polyacrylamide gels (57). Following electrophoretic transfer of proteins onto PVDF membranes (IPVH00010, MilliporeSigma), nonspecific binding was blocked by incubation with 5% skim milk, and then membranes were incubated with primary antibodies against CASP3 (9662, Cell Signaling Technology [CST]), cleaved CASP3 (9661, CST), CASP7 (9492, CST), cleaved CASP7 (9491, CST), CASP8 (AG-20T-0138-C100, AdipoGen), cleaved CASP8 (8592, CST), IRF1 (8478, CST), P-ERK (9101, CST), ERK (9102, CST), P-IκBα (9241, CST), IκBα (9242, CST), P-STAT3 Tyr705 (9131, CST), STAT3 (9139, CST), and…”
Section: Methodsmentioning
confidence: 99%
“…For immunoblot analysis of signaling components, supernatants were removed, and cells were washed once with PBS, followed by lysis in RIPA buffer and sample loading buffer. Proteins were separated by electrophoresis through 8%-12% polyacrylamide gels (57). Following electrophoretic transfer of proteins onto PVDF membranes (IPVH00010, MilliporeSigma), nonspecific binding was blocked by incubation with 5% skim milk, and then membranes were incubated with primary antibodies against CASP3 (9662, Cell Signaling Technology [CST]), cleaved CASP3 (9661, CST), CASP7 (9492, CST), cleaved CASP7 (9491, CST), CASP8 (AG-20T-0138-C100, AdipoGen), cleaved CASP8 (8592, CST), IRF1 (8478, CST), P-ERK (9101, CST), ERK (9102, CST), P-IκBα (9241, CST), IκBα (9242, CST), P-STAT3 Tyr705 (9131, CST), STAT3 (9139, CST), and…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study has determined important roles for RIPK1, TNF, and myeloid differentiation primary response protein 88 (MyD88) signaling in the complete rescue of skin inflammation in Sharpin cpdm mice. [141][142][143] Together, these studies show that Sharpin is a crucial regulator of both apoptotic and necroptotic cell death pathways in epidermal cells. Moreover, these findings have been further strengthened by the demonstration that MyD88 deficiency.…”
Section: Il-1-related But Inflammasome-independent Autoinflammatory Dmentioning
confidence: 74%
“…Sharpin cpdm inflammasome component–deficient mice still develop a full spectrum of disease, suggesting that the IL‐1 signaling pathway may play only a minor role in disease progression. Another recent study has determined important roles for RIPK1, TNF, and myeloid differentiation primary response protein 88 (MyD88) signaling in the complete rescue of skin inflammation in Sharpin cpdm mice . Together, these studies show that Sharpin is a crucial regulator of both apoptotic and necroptotic cell death pathways in epidermal cells.…”
Section: Il‐1‐related But Inflammasome‐independent Autoinflammatory Dmentioning
confidence: 95%
“…However, the genetic deletions of caspase 8 and Rip3k in mice (Sharpin cpd/cpdm /Casp8 +/− /Rip3k −/− ) completely alleviated the phenotype [62]. Recently, Sharma and coworkers showed that the genetic ablation of MyD88 in Sharpin-deficient cpdm mice (Sharpin cpd/cpdm /Myd88 −/− ) completely and partially rescued the skin lesions and systemic inflammation, respectively [63]. Interestingly, they proposed that gut microbiota may play a role in inflammation induction in cpdm mice.…”
Section: Lubac-mediated Regulation Of Cell Deathmentioning
confidence: 99%